A preliminary study on spider diversity from a house hold garden (artificial mixed plantation) in West Tripura, India - Dey, Animesh; Debnath, Susmita; Debbarma, Biplab; PS, Chaudhuri (Journal of Research in Biology, 2013)
Insects are the largest taxonomic group in the animal kingdom and their significant role in ecology needs no description. Spiders are exclusively predatory, hence can play a very important role in regulation of insect population in any ecosystem. Comprehensive study of spider fauna of Tripura has not been carried out yet. In our present study, we are attempting to provide relevant information regarding spiders. This information may serve as the baseline documentation for future studies in Tripura. A survey was carried out during July 2011 to January 2012 in a house garden (artificial mixed plantation) in Khayerpur of west Tripura district. A total of 47 spider species belonging to 36 genera of 14 families were collected. Among all the families, Salticidae dominated the studied assemblage and represents approximately 38% of the total species collected.